Clinical Utility of the Serum Level of Lipoprotein-Related Phospholipase A2 in Acute Ischemic Stroke With Cerebral Artery Stenosis - Cao, Jing; Yan, Ping; Zhou, Yajun; Zhou, Xia; Sun, Zhongwu; Zhu, Xiao-Qun (Frontiers in Neurology, 2021)
We aimed to study the clinical utility of serum lipoprotein-associated phospholipase A2 (Lp-PLA2) in acute ischemic stroke (AIS) with cerebral artery stenosis (CAS). We included 200 AIS patients and 90 healthy controls in this study. AIS patients were classified into 3 subgroups depending on the severity of CAS. They were also classified based on the stability of the carotid plaques. Spearman correlation analysis was performed to determine the correlation relationship between the level of Lp-PLA2 and neurologic injury. Binary logistic regression analysis was performed to determine the independent risk factors for AIS. Receiver operating characteristic (ROC) analysis was performed to assess the diagnostic value of Lp-PLA2 for AIS and for the degree of CAS. We found that the serum level of Lp-PLA2 in AIS patients was significantly higher than that in the control group. Lp-PLA2 was further identified as an independent risk factor for AIS. In addition, serum Lp-PLA2 level was the highest in AIS patients with severe CAS or occlusion. Lp-PLA2 level was higher in AIS patients with unstable plaques and in AIS patients with moderate to severe neurological injury. Lp-PLA2 level was positively correlated with National Institutes of Health Stroke Scale (NIHSS) score. The ROC curve indicated that serum Lp-PLA2 level has an excellent diagnostic value for AIS and severe stenosis. Based on these results we conclude that Lp-PLA2 could be a potential biomarker to complement the current imagine methods in the prediction and diagnosis of AIS. An elevated Lp-PLA2 level is also correlated with carotid plaque instability, severe neurological injury and cerebrovascular stenosis. Future longitudinal studies are needed to determine whether there is a causative relationship between Lp-PLA2 and AIS.